Qualitative and quantitative determination of one process- related impurity of Dapagliflozin Propandiol Monohydrate as raw material - محمد هارون; يوسف الأحمد; علي اسماعيل (Latakia University Journal -Medical Sciences Series, 2022)
A novel, simple, sensitive and less time consumption RP-HPLC has been developed and validated for impurity profiling of dapagliflozin propandiol monohydrate as raw material. The method used BDS Hypersil C18 (150mm, 4.6mm, 5µm). The mobile phase consisted of A (Phosphate Buffer adjusted pH to 3.2 using orthophosphoric acid) and B (Acetonitrile). Gradient elution system has been used with 1mL/min flow rate. Detection was carried out using PDA at 240nm. The results of this method showed the presence of an impurity exceeding 0.1% in one of the samples marketed for the active substance then this impurity was isolated by preparative chromatography technique and its structure was determined using FTIR spectroscopy, H1-NMR, C13-NMR spectroscopy, and MS mass spectrometry. Isolated impurity has been identified as dapagliflozin tetraacetate, which is one of the intermediate products in the preparation of this active pharmaceutical ingredient (API).